Review of ecological valuation and equivalency analysis methods for assessing temperate nearshore submerged aquatic vegetation - Pausch, Rachel E (Conservation biology : the journal of the Society for Conservation Biology, 2025)
© 2024 The Author(s). Conservation Biology published by Wiley Periodicals LLC on behalf of Society for Conservation Biology.